A Survey on VANETs: Challenges and Solutions - Hadi Saleh, Hassan; Talib Hasoon, Saad (International Journal of Engineering and Technology, 2018)
Vehicular Ad-hoc Network (VANET) is an advanced style and subcategory of a Mobile Ad hoc Network (MANET), the main objective of VANET's is to create an Intelligent Transport System (ITS), to reduce traffic congestion, accidents or assistance as gates to other networks such as the Internet. VANET is responsible for the communication between moving vehicles in a certain environment. A vehicle can communicate with another vehicle directly which is termed Vehicle to Vehicle (V2V) communication, or a vehicle can communicate to an infrastructure such as a Road Side Unit (RSU), identified as Vehicle-to-Infrastructure (V2I). VANET networks have now been established as reliable networks used by vehicles for communication on highways or urban environments. The goal of VANET is to help a group of vehicles to establish and maintain a network of communications between them without using any central base station. Along with benefits, there are a large number of challenges facing VANET.Â In this research, we present a comprehensive review of the challenges facing these networks with some of the proposed solutions, Researchers will gain best understand of VANETs challenges and research trends from the study.Â Â